Effects of TPACK-Based Problem-Based Learning Integrated with Kenduri Blang Ethnoscience on Elementary Students' Critical Thinking and Collaboration Skills - Yasir Rizqa; Irdalisa Irdalisa; Nadia Aldyza (Sakura Digital Nusantara, 2026)
This study examined the effects of TPACK-based Problem-Based Learning (PBL) integrated with the Kenduri Blang ethnoscience on the critical thinking and collaboration skills of fifth-grade elementary school students in ecosystem learning. A quasi-experimental study using a non-equivalent control group design was conducted with 30 students, including 15 in the experimental group and 15 in the control group. Data were collected using a validated critical thinking test and a collaboration observation sheet and analyzed using descriptive statistics and independent-samples t-tests. The results showed that the experimental group outperformed the control group in both critical thinking and collaboration. The mean post-test critical thinking score was 85.40 in the experimental group and 52.53 in the control group (t = 12.843, p < 0.001). Similarly, the mean collaboration score was 16.40 in the experimental group and 12.93 in the control group (t = 6.566, p < 0.001). These findings indicate that integrating TPACK, PBL, and the Kenduri Blang ethnoscience effectively promotes higher-order thinking and collaborative learning through technology-supported and culturally relevant instruction. The findings provide practical guidance for teachers and curriculum developers seeking to integrate local ethnoscience into science learning. However, the relatively small sample, single-school setting, and short intervention period may limit the generalizability of the findings. This study contributes to the literature by demonstrating the value of combining TPACK, Problem-Based Learning, and local ethnoscience within a single instructional framework for elementary science education.